4x-(9-3x)=8x-men

Simple and best practice solution for 4x-(9-3x)=8x-men equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-(9-3x)=8x-men equation:


Simplifying
4x + -1(9 + -3x) = 8x + -1men
4x + (9 * -1 + -3x * -1) = 8x + -1men
4x + (-9 + 3x) = 8x + -1men

Reorder the terms:
-9 + 4x + 3x = 8x + -1men

Combine like terms: 4x + 3x = 7x
-9 + 7x = 8x + -1men

Reorder the terms:
-9 + 7x = -1emn + 8x

Solving
-9 + 7x = -1emn + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-9 + 7x + -8x = -1emn + 8x + -8x

Combine like terms: 7x + -8x = -1x
-9 + -1x = -1emn + 8x + -8x

Combine like terms: 8x + -8x = 0
-9 + -1x = -1emn + 0
-9 + -1x = -1emn

Add '9' to each side of the equation.
-9 + 9 + -1x = 9 + -1emn

Combine like terms: -9 + 9 = 0
0 + -1x = 9 + -1emn
-1x = 9 + -1emn

Divide each side by '-1'.
x = -9 + emn

Simplifying
x = -9 + emn

See similar equations:

| -13+x=54 | | (X+3)(X+9)=0 | | 2a/3-4-3=-2/3 | | -19p=-57 | | -(k+5)=-6k | | -222=-6x-6(x+25) | | 4x=2+8x | | 35/6+x=7 | | 6x^2-17x+13=20x^12-32 | | 9+4+x=8+5 | | 12x+10+y=180 | | 7x+3=8x+9 | | b^2+16b+64=7 | | X^2-10x+1=23 | | 2(7+6x)=34+8x | | 7x-2(5x-20)=61 | | 5-2n=12 | | -4/.5=c | | 10x-8x=30 | | 6p-12=-8+7p | | 8(7p-6)= | | 4s-8=8+8s | | (4b+3)(b-12)= | | -35=-7x+7 | | 5m^2+2=m | | 4/5y+7=47 | | 15-4x=23 | | -28/7/20=c | | 18=-36+9y | | 2.6+y=2y+8.6 | | -2(X-3)=5X-8 | | 3/5-2/3x=29 |

Equations solver categories